PENINGKATAN PENDIDIKAN CIVIC SKILL TENAGA KERJA DI ERA REVOLUSI INDUSTRI 4.0 - Zaki, Ammar; Kamza, Muhjam; Akhyar, Akhyar; Azis, Daska; Hidayat, Tita Nurmalinasari (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
This study aims to provide an overview of improving civic skills in the workforce. The era of the industrial revolution 4.0 has had an impact on the world of employment, which is required for citizens to adapt in order to maintain their lives. At this point it is necessary to make preparations for citizens to increase their competence. BLK is a state’s tool that functions as a facility for increasing citizen skills. The research was conducted at BLK Aceh Province. This study uses a qualitative approach. Data collection using techniques such as observations, interviews, and document analysis. Participants in this study were instructors and trainees. The results of the study show that BLK has improved civic skills through the training program implemented